Identification of transforming growth factor-beta-regulated microRNAs and the microRNA-targetomes in primary lung fibroblasts. - Jennie Ong; Wim Timens; Vijay Rajendran; Arjan Algra; Avrum Spira; Marc E Lenburg; Joshua D Campbell; Maarten van den Berge; Dirkje S Postma; Anke van den Berg; Joost Kluiver; Corry-Anke Brandsma (PLoS ONE)
Background Lung fibroblasts are involved in extracellular matrix homeostasis, which is mainly regulated by transforming growth factor-beta (TGF-β), and are therefore crucial in lung tissue repair and remodeling. Abnormal repair and remodeling has been observed in lung diseases like COPD. As miRNA levels can be influenced by TGF-β, we hypothesized that TGF-β influences miRNA expression in lung fibroblasts, thereby affecting their function. Materials and methods We investigated TGF-β1-induced miRNA expression changes in 9 control primary parenchymal lung fibroblasts using miRNA arrays. TGF-β1-induced miRNA expression changes were validated and replicated in an independent set of lung fibroblasts composted of 10 controls and 15 COPD patients using qRT-PCR. Ago2-immunoprecipitation followed by mRNA expression profiling was used to identify the miRNA-targetomes of unstimulated and TGF-β1-stimulated primary lung fibroblasts (n = 2). The genes affected by TGF-β1-modulated miRNAs were identified by comparing the miRNA targetomes of unstimulated and TGF-β1-stimulated fibroblasts. Results Twenty-nine miRNAs were significantly differentially expressed after TGF-β1 stimulation (FDR<0.05). The TGF-β1-induced miR-455-3p and miR-21-3p expression changes were validated and replicated, with in addition, lower miR-455-3p levels in COPD (p<0.05). We identified 964 and 945 genes in the miRNA-targetomes of unstimulated and TGF-β1-stimulated lung fibroblasts, respectively. The TGF-β and Wnt pathways were significantly enriched among the Ago2-IP enriched and predicted targets of miR-455-3p and miR-21-3p. The miR-455-3p target genes HN1, NGF, STRADB, DLD and ANO3 and the miR-21-3p target genes HHEX, CHORDC1 and ZBTB49 were consistently more enriched after TGF-β1 stimulation. Conclusion Two miRNAs, miR-455-3p and miR-21-3p, were induced by TGF-β1 in lung fibroblasts. The significant Ago2-IP enrichment of targets of these miRNAs related to the TGF-β and/or Wnt pathways (NGF, DLD, HHEX) in TGF-β1-stimulated fibroblasts suggest a role for these miRNAs in lung diseases by affecting lung fibroblast function.